FORMATION OF MUSIC AND AESTHETIC ORIENTATIONS OF FUTURE TEACHERS IN EXTRACURRICULAR ACTIVITIES ON MATERIALS OF INTEGRATION OF ARTS (Pedagogy of Higher and Secondary Education, 2022)
In the paper the art integration is considered as a necessary condition offormation of musical aesthetic value.